Observation of electrochemically active Fe3+/Fe4+ in LiCo0.8Fe0.2MnO4 by in situ Mössbauer spectroscopy and X-ray absorption spectroscopy. Issue 1 (6th December 2018) - Dräger, Christoph; Sigel, Florian; Witte, Ralf; Kruk, Robert; Pfaffmann, Lukas; Mangold, Stefan; Mereacre, Valeriu; Knapp, Michael; Ehrenberg, Helmut; Indris, Sylvio
Abstract : The reversible oxidation process of Fe 3+ to Fe 4+ in LiCo0.8 Fe0.2 MnO4 has been observed by in situ Mössbauer spectroscopy. Abstract : LiCo0.8 Fe0.2 MnO4 has been investigated as an active material for the positive electrode in lithium-ion batteries (LIBs) with a discharge potential of around 5 V ( vs. Li + |Li). After synthesis by a Pechini based sol–gel route, the structural and morphological properties have been investigated by X-ray diffraction, scanning electron microscopy, 7 Li MAS NMR spectroscopy, and 57 Fe Mössbauer spectroscopy. With galvanostatic cycling, it was possible to obtain a specific discharge capacity of 117 mA h g −1, which is more than 80% of the theoretical capacity. The lithium extraction/insertion mechanism has been characterized by in situ synchrotron powder diffraction. The reversible oxidation process of Fe 3+ to Fe 4+ has been observed by in situ Mössbauer spectroscopy and in situ XAS measurements.